BINWIN Revitalization: KMA Requires 30 Hours of Spaced Learning for Family Skills - Umroh Widjayanti (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This Policy Paper discusses the disruption and instability of households in Indonesia, as reflected in the rising divorce rate, highlighting the failure of premarital policy interventions. In East Java, the high number of divorce cases indicates dysfunction in the implementation of the Marriage Guidance Program (BINWIN) organized by the Ministry of Religious Affairs. Problem identification reveals that the ineffectiveness of this program stems from three policy roots: (1) Material design dominated by normative-theoretical aspects and minimal application skills (conflict resolution and financial management); (2) Delivery methods that tend to be passive, one-way, and not in accordance with the principles of Andragogy; and (3) Limited duration of guidance that is very short (10-16 hours), which violates the Principle of Program Intensity. This policy formulation method uses a qualitative approach through regulatory document analysis and literature review. Critical evaluation is conducted based on the analysis of the policy's root causes, followed by scoring of policy alternatives using William N. Dunn's criteria. The scoring results determine that changes in methodology and duration are the most optimal interventions for increasing effectiveness. The proposed recommendation is to revise Minister of Religious Affairs Decree No. 189 of 2021, setting a minimum duration of 30 effective hours and requiring implementation in a Distance Learning format for at least four weeks before the marriage ceremony. This policy aims to transform BINWIN from an administrative formality into an effective skills intervention in building family resilience.